2015
DOI: 10.2141/jpsa.0140191
|View full text |Cite
|
Sign up to set email alerts
|

Effect of <i>Cordyceps Militaris </i>Waster Medium on Production Performance, Egg Traits and Egg Yolk Cholesterol of Laying Hens

Abstract: Cordyceps militaris waster medium (CMWM) is a by-product of the edible portion of the fruiting body of Cordyceps fungi. This study was conducted to investigate the effects of the CMWM on the production performance, egg quality and egg yolk cholesterol of laying hens. An in vitro study showed that the reducing power of the CMWM extracts increased linearly with its concentration; at a concentration of 4.0 mg/mL, it reached a level of roughly 60% ascorbic acid at 0.5 mg/mL, while inhibition of lipid peroxidation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 36 publications
(33 reference statements)
1
14
1
Order By: Relevance
“…In the present study, the differences in the egg quality between the three groups were insignificant. Similarly, scholars observed that supplementing a diet with C. militaries waster medium did not improve eggshell thickness and egg shell strength (Wang et al, 2015).…”
Section: Effects Of Cmp On Egg Production and Egg Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, the differences in the egg quality between the three groups were insignificant. Similarly, scholars observed that supplementing a diet with C. militaries waster medium did not improve eggshell thickness and egg shell strength (Wang et al, 2015).…”
Section: Effects Of Cmp On Egg Production and Egg Qualitymentioning
confidence: 99%
“…Researchers emphasized that feeding laying hens with C. militaries waster medium decreased significantly feed conversion ratio (FCR) and increased egg production. They also showed that ascorbic acid and C. militaries waster mediuman have approximately the same reducing power (Wang et al, 2015 ) Cifticiet al indicated that ascorbic acid can partially inhibit adverse oxidative protein denaturation and improve nutrient digestibility and FCR (Ciftici,et al,2005). As such, the feed-egg ratio of the hens receiving the added CMP in the present study was likely to decrease and egg production to increased.…”
Section: Effects Of Cmp On Egg Production and Egg Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…The mushroom, Cordyceps militaris, was used in layer diets to evaluate the performance and egg yolk cholesterol level by Wang et al [57]. The results showed significantly lower (p < 0.05) egg cholesterol in mushroom fed groups with 1% and 2% levels than the control fed groups.…”
Section: Application Of Medicinal Mushrooms On Performance and Egg Qumentioning
confidence: 99%
“…Moreover, it also activates the development of reactive substances, such as enzymes and vitamins in embryos ( Er et al, 2007 ). Evidently, the source, spectrum, intensity and regimen of artificial light supplementation are critical factors for the modern management of the poultry industry ( Borille et al, 2013 ; Morrill et al, 2014 ; Lee et al, 2015 ; Wang et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%